Greek renal nurses' attitudes towards death - Zyga, Sofia; Malliarou, Maria Adamantia; Lavdaniti, Maria; Athanasopoulou, Maria; Sarafis, Pavlos (My University, 2011)
This study aims to assess how Greek renal nurses feel about death and examine any relationships between their attitudes and demographic factors. Design: Descriptive quantitative study. The sample comprised of 49 nurses. Methodology: Voluntary and anonymous completion of the Death Attitude Profile-Revised and a demographic questionnaire. Results: 44 respondents were female and 5 were male with a mean age of 25.80 years. The mean nursing experience was 10.9 years. Nursing experience and age were the variables most likely to predict nurses' attitudes towards death. Nurses with specific education on palliative care had less difficulty talking about death and dying and did not have a fear of death. The Hospital-based teams (known as palliative care teams, supportive care teams or symptom assessment teams) had statistically significant different relationships with fear of death and neutral acceptance scores. Conclusions: It is recommended to include education on death and care of the dying in the nursing degree course in order for nurses who are giving terminal phase patient care to be better able deal with issues that death evolves.
Keywords: Education; Haemodialysis; Nursing; Psychosocial